A case series analysis on the clinical experience of Impella 5.5® at a large tertiary care centre. (17th August 2021) - Kennel, Peter J.; Lumish, Heidi; Kaku, Yuji; Fried, Justin; Kirtane, Ajay J.; Karmpaliotis, Dimitri; Takayama, Hiroo; Naka, Yoshifumi; Sayer, Gabriel; Uriel, Nir; Takeda, Koji; Masoumi, Amirali
Abstract: Aims: We aimed to detail the early clinical experience with pVAD 5.5 at a large academic medical centre. Impella® 5.5 (Abiomed) is a temporary peripherally inserted left ventricular assist device (pVAD) used for the treatment of cardiogenic shock (CS). This system has several modifications aimed at improving deliverability and durability over the pVAD 5.0 system, but real‐world experience with this device remains limited. Methods and results: We collected clinical and outcome data on all patients supported with pVAD 5.5 at our centre between February and December 2020, including procedural and device‐related complications. Fourteen patients with pVAD 5.5 were included. Aetiology of CS was acute myocardial infarction ( n = 6), decompensated heart failure ( n = 6), suspected myocarditis ( n = 1), and post‐cardiotomy CS ( n = 1). Four patients received pVAD 5.5 after being on inotropes alone, two were escalated from intra‐aortic balloon pump, two were escalated from pVAD CP, and six patients were transitioned to pVAD 5.5 from extracorporeal membrane oxygenation. Median duration of pVAD 5.5 support was 12 (interquartile range 7, 25) days. Complications included axillary insertion site haematoma ( n = 3), acute kidney injury ( n = 3), severe thrombocytopenia ( n = 1), and stroke ( n = 1). No valve injury or limb complications occurred. Survival to device explant for recovery or transition to another therapy was 11/14 (79%) patients. Conclusions: In this early experience of the pVAD 5.5, procedural and device‐related complications were observed but were manageable, and overall survival was high in this critically ill cohort, particularly when the device was used as a bridge to other therapies.